Spinal Cord MR Diffusion Properties in Patients with Degenerative Cervical Cord Compression - Keřkovský, Miloš; Bednařík, Josef; Jurová, Barbora; Dušek, Ladislav; Kadaňka, Zdeněk; Kadaňka, Zdeněk; Němec, Martin; Kovaľová, Ivana; Šprláková-Puková, Andrea; Mechl, Marek (Journal of neuroimaging, 2017)
BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) has previously been used as a biomarker of myelopathy in patients with degenerative cervical cord compression (DCCC). However, many factors may affect the diffusion properties of the spinal cord. This prospective study seeks to identify sources of variability in spinal cord DTI parameters in both DCCC patients and healthy subjects. METHODS: The study group included 130 patients with DCCC confirmed by magnetic resonance imaging and 71 control subjects without signs of DCCC. DTI data of the cervical spine were acquired in all subjects. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values were measured at different levels of the spinal cord (SCLs). Statistical data analysis was then used to determine diffusion parameters in terms of age, sex, SCL, and spinal cord compression. RESULTS: Significant variations in FA and ADC values emerged when several spinal cord levels were mutually compared in the control group. FA values correlated significantly with age in the DCCC group and sex had a significant influence on ADC values in both groups. The two diffusion parameters in the DCCC group differed significantly between patients with clinical signs of mild-to-moderate myelopathy compared with asymptomatic patients, and correlated with measurements of spinal canal morphology. CONCLUSIONS: Diffusion parameters of the cervical spinal cord were thus shown to respond significantly to spinal cord compression, but were subject to interaction with several other factors including sex, age, and SCL. These findings may be important to the interpretation of DTI measurements in individual patients.
Keywords: komprese míchy; Magnetic resonance imaging; krční mícha; Middle Aged; mužské pohlaví; Diffusion Tensor Imaging; diffusion tensor imaging; Prospective Studies; Spinal Cord Compression; Cervical Cord; ženské pohlaví; Humans; prospektivní studie; zobrazování difuzních tenzorů; lidé středního věku; degenerative cervical cord compression; degenerative cervical myelopathy; Female; lidé; Male